Ferritic stainless steel material for battery part and method for manufacturing the same and battery part
A ferritic stainless steel material with controlled oxide inclusions and specific composition addresses the issue of high-temperature fatigue in battery parts, improving safety by reducing thermal runaway risk and extending the time for evacuation.
Patent Information
- Application Number
- JP2023107465
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing stainless steel materials for battery parts, particularly those used in lithium-ion secondary batteries, lack sufficient high-temperature fatigue properties, leading to potential damage, short-circuiting, and thermal runaway due to impacts or temperature fluctuations, which is critical for ensuring safety and evacuation time in vehicles.
A ferritic stainless steel material with controlled oxide inclusions and specific elemental composition, manufactured through a precise melting and refining process with controlled time and temperature conditions, ensuring cleanliness of inclusions within a specified range.
The material exhibits excellent high-temperature fatigue properties, reducing the risk of thermal runaway and extending the time before a fire occurs, thereby enhancing safety in lithium-ion secondary batteries.
Smart Images

Figure 2025006580000001 
Figure 2025006580000002 
Figure 2025006580000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel material for battery components, a manufacturing method thereof, and a battery component. [Background technology]
[0002] Among various types of batteries, lithium-ion secondary batteries have been used as power sources for mobile phones, smartphones, notebook computers, and other devices due to their high voltage, light weight, high energy density, and high power density. On the other hand, due to the need to reduce greenhouse gases (CO2) caused by global warming and issues with petroleum resources, regulations on automobile CO2 emissions and fuel efficiency have been put into place, leading to the development of vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (EVs), and fuel cell vehicles (FCVs), which also use lithium-ion secondary batteries as their power sources.
[0003] Lithium-ion secondary batteries for vehicles are classified into cylindrical, rectangular, laminated, etc., depending on their shape, but rectangular and laminated types are widely used from the viewpoint of space saving. In a rectangular lithium-ion secondary battery, a laminated body in which a separator is arranged between a positive electrode and a negative electrode is housed in a rectangular case mainly made of aluminum. A cover member mainly made of aluminum is arranged at the opening of the rectangular case, and is closed by welding to the rectangular case.
[0004] Lithium ion secondary batteries for vehicles are required to have increased battery capacity, energy density, and power density in order to extend the driving range, so the reliability of battery components such as square cases and lid members is also a very important issue. For this reason, battery components are evaluated in nail penetration tests, crash tests, external short tests, etc. in cases where the positive and negative electrodes are short-circuited internally or externally, or where a non-aqueous electrolyte reacts and becomes abnormally high due to a sudden increase in temperature. However, in the case of battery components made of aluminum, the evaluation results are often insufficient due to their low high-temperature strength and melting point. In particular, in the case of large-capacity lithium ion secondary batteries, square cases made of stainless steel are used in some cases because they are more reliable than battery components made of aluminum.
[0005] For example, as a stainless steel material used for battery components, Patent Document 1 discloses a method for manufacturing a lithium ion secondary battery case made of austenitic stainless steel foil. Patent Document 2 discloses the application of an austenitic stainless steel sheet to a battery case for an electric vehicle having excellent heat resistance. Patent Document 3 discloses a ferritic stainless steel containing 16.0 to 32.0 mass % of Cr as an electrode material and electrode case for a large-capacity battery. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6090923 [Patent Document 2] Japanese Patent Application Publication No. 10-188922 [Patent Document 3] JP 2009-167486 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the stainless steel materials disclosed in Patent Documents 1 to 3 do not have sufficient high-temperature fatigue properties when used in battery components. Therefore, when a lithium-ion secondary battery is subjected to an impact due to a collision accident or the like, it is likely to break, short circuit, and lead to thermal runaway. Even in a lithium-ion secondary battery in which thermal runaway does not occur, thermal runaway is likely to occur if the battery components are deformed due to fatigue caused by temperature rise and vibration. If the temperature rises to about 800°C due to thermal runaway, a fire may break out in a short time. In this way, high-temperature fatigue properties are important for battery components in order to extend the time from the occurrence of thermal runaway due to a collision accident or the like to a fire and to ensure sufficient time for people to evacuate.
[0008] The present invention has been made to solve the above problems, and has an object to provide a ferritic stainless steel material for battery components having excellent high-temperature fatigue properties, a manufacturing method thereof, and a battery component. [Means for solving the problem]
[0009] The present inventors have conducted extensive research into ferritic stainless steel materials and have found that the cleanliness of oxide-based inclusions is closely related to high-temperature fatigue properties. The present inventors have also found that ferritic stainless steel materials having such characteristics can be obtained by controlling the time from the end of heating in the melting and refining process to the start of casting in the casting process and the rate of temperature reduction of molten steel during that time. The present invention was completed based on these findings.
[0010] That is, the present invention provides a steel sheet comprising, on a mass basis, 0.001-0.020% C, 0.001-0.020% N, 0.01-0.60% Si, 0.01-0.70% Mn, 0.001-0.050% P, 0.0001-0.0014% S, 9.5-18.5% Cr, 0.001-0.700% Ni, 0.001-1.200% Cu, 0.03-0.27% Ti, 0.001-0.200% Nb, and 0.003-0.180% Al, with the remainder being Fe and impurities; The cleanliness of oxide inclusions measured by the point counting method specified in Annex JA of JIS G0555:2020 is 0.004 to 0.200%, and the cleanliness of B1 inclusions is 0.100% or less. This is a ferritic stainless steel material for battery components that satisfies the following formula (1). 7.7×(C+N)≦Ti+Nb≦0.340 (1) In the formula, each element symbol represents the content (mass %) of each element.
[0011] The present invention also provides a method for producing the ferritic stainless steel material for battery components, comprising the steps of: The method includes a melting and refining process and a casting process, In this manufacturing method, the time from the end of heating in the melting and refining step to the start of casting in the casting step is 30 to 120 minutes, and the temperature of the molten steel is lowered at a rate of 0.20 to 2.50° C. / min during that time.
[0012] Furthermore, the present invention relates to a battery component comprising the above-mentioned ferritic stainless steel material for battery components. Effect of the Invention
[0013] According to the present invention, it is possible to provide a ferritic stainless steel material for battery components having excellent high-temperature fatigue properties, a manufacturing method thereof, and a battery component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified. (1) Ferritic stainless steel for battery components The ferritic stainless steel material for battery components according to an embodiment of the present invention (hereinafter sometimes abbreviated as "ferritic stainless steel material") contains C: 0.001-0.020%, N: 0.001-0.020%, Si: 0.01-0.60%, Mn: 0.01-0.70%, P: 0.001-0.050%, S: 0.0001-0.0014%, Cr: 9.5-18.5%, Ni: 0.001-0.700%, Cu: 0.001-1.200%, Ti: 0.03-0.27%, Nb: 0.001-0.200%, Al: 0.003-0.180%, with the remainder being Fe and impurities.
[0015] In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of ferritic stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. Examples of impurities include O, As, Pb, etc. It is preferable to reduce impurities as much as possible. In addition, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape.
[0016] Furthermore, in this specification, "ferritic" means that the metal structure is mainly ferritic at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic (e.g., austenite and martensite). However, "ferritic" does not include a multi-phase structure of ferritic and austenite phases, a multi-phase structure of ferritic and martensite phases, or a multi-phase structure of ferritic, austenite, and martensite phases.
[0017] The ferritic stainless steel material according to the embodiment of the present invention may contain, as necessary, Mo: 0.01 to 2.50%, V: 0.01 to 0.50%, Zr: 0.01 to 0.50%, B: 0.0001 to 0.0050%, Ca: 0.0001 to 0.0100%, W: 0.01 to 2.50%, Sn: 0.01 to 0.50%, Co: 0.01 to 0.5 It may further contain one or more selected from the group consisting of 0%, Mg: 0.0001 to 0.0100%, Sb: 0.001 to 0.300%, REM: 0.001 to 0.500%, Ga: 0.0001 to 0.3000%, Ta: 0.001 to 1.000%, Hf: 0.001 to 1.000%, and Bi: 0.001 to 0.200%. Each component will be described in detail below.
[0018] <C:0.001~0.020%> If excessive C is added, the fixation of C is insufficient, resulting in sensitization, and fatigue properties cannot be secured at high temperatures (e.g., 600°C). Furthermore, if a large amount of C is added, the corrosion resistance decreases and the Ti content required to fix C also increases. Therefore, the C content is set to 0.020% or less, preferably 0.018% or less, and more preferably 0.015% or less. However, since an excessive reduction in C leads to an increase in refining costs, the C content is set to 0.001% or more, and preferably 0.002% or more.
[0019] <N:0.001~0.020%> Similarly to C, excessive addition of N leads to sensitization due to insufficient fixation of N, and fatigue properties cannot be secured at high temperatures (e.g., 600°C). In addition, addition of a large amount of N reduces corrosion resistance and increases the Ti content required to fix N. Therefore, the N content is set to 0.020% or less, preferably 0.018% or less, and more preferably 0.015% or less. However, since excessive reduction of N leads to an increase in refining costs, the N content is set to 0.001% or more, and preferably 0.002% or more.
[0020] <Si:0.01~0.60%> When a large amount of Si is added, the high-temperature strength increases, but the toughness decreases when an impact is applied due to a collision accident or during processing, and the high-temperature fatigue properties decrease. Therefore, the Si content is set to 0.60% or less, preferably 0.55% or less, and more preferably 0.50% or less. On the other hand, Si is an element effective for deoxidization and solid solution strengthening. From the viewpoint of obtaining these effects, the Si content is set to 0.01% or more, preferably 0.02% or more.
[0021] <Mn:0.01~0.70%> Like Si, when Mn is added in excess, the high-temperature strength increases, but the toughness decreases when an impact is applied due to a collision accident or during processing, and the high-temperature fatigue properties decrease. Therefore, the Mn content is set to 0.70% or less, preferably 0.65% or less, more preferably 0.60% or less, and even more preferably 0.40% or less. However, since an excessive reduction in Mn leads to an increase in refining costs, the Mn content is set to 0.01% or more, preferably 0.05% or more.
[0022] <P:0.001~0.050%> If excessive P is added, the high-temperature strength increases, but the toughness decreases when an impact is applied due to a collision accident or during processing, and the high-temperature fatigue properties decrease. Therefore, the P content is set to 0.050% or less, preferably 0.040% or less. However, since an excessive reduction in P content increases the steelmaking cost due to the selection of raw materials, the P content is set to 0.001% or more, preferably 0.005% or more.
[0023] <S:0.0001~0.0014%> If excessive S is added, high-temperature strength increases, but toughness decreases when an impact is applied due to a collision accident or during processing, and high-temperature fatigue properties decrease. Therefore, the S content is set to 0.0014% or less, preferably 0.0013% or less, and more preferably 0.0012% or less. However, since an excessive reduction in S increases steelmaking costs due to the selection of raw materials, etc., the S content is set to 0.0001% or more, and preferably 0.0002% or more.
[0024] <Cr:9.5~18.5%> Cr is an element necessary for ensuring corrosion resistance, which is a basic characteristic of ferritic stainless steel materials. However, if excessive Cr is added, although the high-temperature strength increases, the toughness decreases and the high-temperature fatigue properties decrease when an impact is applied due to a collision accident or during processing. Therefore, the Cr content is set to 18.5% or less, preferably less than 18.0%. On the other hand, excessive reduction in Cr reduces the high-temperature strength and the high-temperature fatigue properties, and the corrosion resistance cannot be sufficiently ensured. Therefore, the Cr content is set to 9.5% or more, preferably 9.8% or more, and more preferably 10.0% or less.
[0025] <Ni:0.001~0.700%> If Ni is added in excess, the high-temperature strength increases, but the toughness decreases when an impact is applied due to a collision accident or during processing, and the high-temperature fatigue properties decrease. Therefore, the Ni content is set to 0.700% or less, preferably 0.600% or less, more preferably 0.550% or less, and even more preferably 0.400% or less. However, excessive reduction in Ni content reduces the high-temperature strength and the high-temperature fatigue properties. Therefore, the Ni content is set to 0.001% or more, preferably 0.002% or more.
[0026] <Cu:0.001~1.200%> If excessive Cu is added, the high-temperature strength increases, but the toughness decreases when an impact is applied due to a collision accident or during processing, and the high-temperature fatigue properties decrease. Therefore, the Cu content is set to 1.200% or less, preferably 1.100% or less, and more preferably 0.400% or less. However, excessive reduction in Cu content reduces the high-temperature strength and the high-temperature fatigue properties. Therefore, the Cu content is set to 0.001% or more, and preferably 0.002% or more.
[0027] <Ti:0.03~0.27%> Excessive addition of Ti increases the amount of coarse carbonitrides, degrading high-temperature fatigue properties. Therefore, the Ti content is set to 0.27% or less, preferably less than 0.25%. However, if the amount of Ti added is too small, the fixation of C and N is insufficient, resulting in sensitization and failure to ensure fatigue properties at high temperatures (e.g., 600°C). Therefore, the Ti content is set to 0.03% or more, preferably 0.05% or more, more preferably 0.10% or more.
[0028] <Nb:0.001~0.200%> If Nb is added excessively, the amount of coarse carbonitrides increases, and the high-temperature fatigue properties are reduced. Therefore, the Nb content is set to 0.200% or less, preferably 0.160% or less, and more preferably less than 0.100%. On the other hand, Nb is an element that combines with C and N to form precipitates and improve workability. Nb is also an element that improves corrosion resistance (especially, the corrosion resistance of the welded portion when welding). In order to obtain the effects of Nb, the Nb content is set to 0.001% or more, and preferably 0.002% or more.
[0029] <Al:0.003~0.180%> If excessive Al is added, the cleanliness of oxide-based inclusions and B1-based inclusions cannot be controlled within a predetermined range, and high-temperature fatigue properties deteriorate. Therefore, the Al content is set to 0.180% or less, preferably 0.170% or less, and more preferably 0.150% or less. If too little Al is added, the oxide-based inclusions decrease, but deoxidation becomes insufficient, the S content increases, and high-temperature fatigue properties deteriorate. Therefore, the Al content is set to 0.003% or more, and preferably 0.010% or more.
[0030] <Mo:0.01~2.50%> Like Cr, Mo is an element that is effective in ensuring corrosion resistance, which is a basic property of ferritic stainless steel materials. To obtain the effects of Mo, the Mo content is set to 0.01% or more, preferably 0.05% or more. However, since excessive addition of Mo increases steelmaking costs and leads to increased strength and reduced elongation, the Mo content is set to 2.50% or less, preferably 2.30% or less, and more preferably 1.30% or less.
[0031] <V:0.01~0.50%、Zr:0.01~0.50%> V and Zr are elements that combine with C and N to suppress the formation of Cr carbonitrides. In order to obtain the effects of V and Zr, the V content and Zr content are each set to 0.01% or more, preferably 0.05% or more. However, since excessive addition of V and Zr reduces workability, the V content and Zr content are each set to 0.50% or less, preferably 0.40% or less, more preferably 0.20% or less.
[0032] <B:0.0001~0.0050%> B is an element that is effective in increasing strength and also suppresses secondary work cracking. To obtain the effects of B, the B content is set to 0.0001% or more, preferably 0.0003% or more. However, since excessive addition of B becomes the starting point for void formation and reduces formability and toughness, the B content is set to 0.0050% or less, preferably 0.0040% or less, and more preferably 0.0030% or less.
[0033] <Ca:0.0001~0.0100%> Ca is an element effective in fixing S and improving hot workability. To obtain the effect of Ca, the Ca content is set to 0.0001% or more, preferably 0.0002% or more. However, since excessive addition of Ca leads to a decrease in corrosion resistance, the Ca content is set to 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0050% or less.
[0034] <W:0.01~2.50%> W is an element that improves corrosion resistance and also acts as a solid solution strengthening element. In order to obtain the effects of W, the W content is set to 0.01% or more, preferably 0.05% or more. However, since excessive addition of W leads to a decrease in workability and toughness, an increase in cost, etc., the W content is set to 2.50% or less, preferably 2.00% or less, more preferably 0.50% or less.
[0035] <Sn:0.01~0.50%> Sn is an element that enhances the repair ability of the passive film of ferritic stainless steel material and enhances corrosion resistance. To obtain the effects of Sn, the Sn content is set to 0.01% or more, preferably 0.02% or more. However, since excessive addition of Sn leads to an increase in strength and a decrease in ductility, the Sn content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0036] <Co:0.01~0.50%> Co is an element that contributes to improving high-temperature strength. In order to obtain the effects of Co, the Co content is set to 0.01% or more, preferably 0.03% or more. However, since excessive addition of Co leads to a decrease in toughness during manufacturing, an increase in costs, and a decrease in workability, the Co content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0037] <Mg:0.0001~0.0100%> Mg is an element added as a deoxidizing element. In addition, Mg contributes to improving manufacturability by refining ferrite grains, improving surface defects called ridging, and improving workability of welds. In order to obtain the effects of Mg, the Mg content is set to 0.0001% or more, preferably 0.0003% or more. However, excessive addition of Mg significantly reduces corrosion resistance and also leads to reduced workability due to coarse MgO, so the Mg content is set to 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0050% or less.
[0038] <Sb:0.001~0.300%> Sb is an element that segregates at grain boundaries and has the effect of increasing high-temperature strength. In order to obtain the effect of Sb, the Sb content is set to 0.001% or more, preferably 0.005% or more. However, since excessive addition of Sb leads to grain boundary cracking during processing and cracking during welding due to the segregation of Sb, the Sb content is set to 0.300% or less, preferably 0.200% or less, and more preferably 0.100% or less.
[0039] <REM:0.001~0.500%> REM (rare earth elements) are elements effective in improving oxidation resistance. In order to obtain the effects of REM, the REM content is set to 0.001% or more, preferably 0.005% or more. However, even if REM is added in excess, the effect is saturated and REM sulfides lead to a decrease in corrosion resistance, so the REM content is set to 0.500% or less, preferably 0.400% or less, and more preferably 0.300% or less. REM follows the general definition. That is, REM refers to two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). REM may be added alone or as a mixture.
[0040] <Ga:0.0001~0.3000%> Ga is an element effective in improving corrosion resistance and suppressing hydrogen embrittlement. To obtain the effects of Ga, the Ga content is set to 0.0001% or more, preferably 0.0005% or more. However, since excessive addition of Ga generates coarse sulfides and leads to a decrease in workability, the Ga content is set to 0.3000% or less, preferably 0.2000% or less, and more preferably 0.1000% or less.
[0041] <Ta:0.001~1.000%、Hf:0.001~1.000%> Ta and Hf are elements effective for improving high-temperature strength. In order to obtain the effects of Ta and Hf, the Ta content and Hf content are each set to 0.001% or more, preferably 0.005% or more. However, since excessive addition of Ta and Hf leads to an increase in manufacturing costs, the Ta content and Hf content are each set to 1.000% or less, preferably 0.800% or less, more preferably 0.500% or less.
[0042] <Bi:0.001~0.200%> Bi is an element effective in improving machinability. To obtain the effect of Bi, the Bi content is set to 0.001% or more, preferably 0.005% or more. However, since excessive addition of Bi leads to an increase in manufacturing costs, the Bi content is set to 0.200% or less, preferably 0.150% or less, and more preferably 0.100% or less.
[0043] The ferritic stainless steel material according to the embodiment of the present invention satisfies the following formula (1). 7.7×(C+N)≦Ti+Nb≦0.340 (1) In the formula, each element symbol represents the content (mass %) of each element. By making Ti+Nb 7.7×(C+N) or more, it is possible to reduce coarse carbonitrides and improve high-temperature fatigue properties. Also, by making Ti+Nb 0.340 or less, it is possible to fix C and N, so that fatigue properties at high temperatures (e.g., 600°C) can be secured.
[0044] The ferritic stainless steel material according to the embodiment of the present invention has a cleanliness of oxide-based inclusions of 0.004 to 0.200%, preferably 0.004 to 0.150%, and more preferably 0.004 to 0.125%, as measured by the point counting method defined in Appendix JA of JIS G0555:2020. By controlling the cleanliness of the oxide-based inclusions within such a range, it is possible to improve high-temperature fatigue properties. If the cleanliness of the oxide-based inclusions exceeds 0.200%, the oxide-based inclusions become the fracture origin, and the high-temperature fatigue properties are deteriorated. On the other hand, if the cleanliness of the oxide-based inclusions is less than 0.004%, deoxidation becomes insufficient, the S content increases, and the high-temperature fatigue properties are deteriorated.
[0045] Here, the types of inclusions contained in the ferritic stainless steel material according to the embodiment of the invention are classified into A-type inclusions, B-type inclusions, and C-type inclusions, as described in Appendix JA of JIS G0555:2020. A-type inclusions are those that have been viscously deformed by processing (sulfides, silicates, etc.), and sulfides are called A1-type inclusions, and oxides such as silicates are called A2-type inclusions. B-type inclusions are granular inclusions that are arranged discontinuously in groups in the processing direction, and oxides such as alumina are called B1-type inclusions, and carbonitrides of Nb, Ti, and Zr are called B2-type inclusions. C-type inclusions are irregularly dispersed without viscous deformation, and oxides are called C1-type inclusions, and carbonitrides of Nb, Ti, and Zr are called C2-type inclusions. Therefore, in this specification, "oxide-based inclusions" means the total of A2-based inclusions, B1-based inclusions and C1-based inclusions among the above classifications. In this specification, the oxide-based inclusions include both deoxidation products generated in the steelmaking process and oxides mixed in from raw materials. Examples of oxide-based inclusions include CaO, MgO, Al2O3, SiO2, TiO2, MnO, Cr2O3, FeO, and MgOAl2O3.
[0046] The ferritic stainless steel material according to the embodiment of the present invention has a cleanliness of B1-based inclusions of 0.100% or less, preferably 0.080% or less, more preferably 0.050% or less, measured by the point counting method specified in Appendix JA of JIS G0555:2020. Since the B1-based inclusions, among oxide-based inclusions, are particularly likely to become fracture initiation points, the high-temperature fatigue properties can be reliably improved by controlling the cleanliness of the B1-based inclusions within the above range. Therefore, if the cleanliness of the B1-based inclusions exceeds 0.100%, the B1-based inclusions become fracture initiation points, and the high-temperature fatigue properties are reduced. The lower limit of the cleanliness of the B1-based inclusions is not particularly limited, but is generally 0.001% or more.
[0047] The thickness of the ferritic stainless steel material according to the embodiment of the present invention is not particularly limited and may be appropriately set according to the required characteristics of the battery component in which the ferritic stainless steel material is used. For example, in consideration of the weight reduction of the ferritic stainless steel material and the battery component formed therefrom, the thickness of the ferritic stainless steel material is preferably 1.00 mm or less. In addition, in consideration of the rigidity of the ferritic stainless steel material and the battery component formed therefrom, the thickness of the ferritic stainless steel material is more preferably 0.20 mm or more. Furthermore, in consideration of the fire resistance and cost of the ferritic stainless steel material and the battery component formed therefrom, the thickness of the ferritic stainless steel material is even more preferably 0.20 to 0.80 mm. Furthermore, in consideration of the weldability of the ferritic stainless steel material and the battery component formed therefrom, the thickness of the ferritic stainless steel material is even more preferably 0.30 to 0.60 mm.
[0048] The ferritic stainless steel material according to the embodiment of the present invention has excellent high-temperature fatigue properties because the composition and the cleanliness of the oxide-based inclusions and B1-based inclusions are controlled. Therefore, the ferritic stainless steel material according to the embodiment of the present invention has excellent resistance to thermal runaway of the lithium-ion secondary battery when the lithium-ion secondary battery is subjected to an impact due to a collision accident or the like. Therefore, the time from the occurrence of thermal runaway due to a collision accident or the like to the outbreak of a fire can be extended, and sufficient time for people to evacuate can be secured. The ferritic stainless steel material according to the embodiment of the present invention can be used as a material for battery components in transportation equipment (particularly automobiles, buses, trains, etc.), but is particularly suitable for use as case and lid members for lithium ion secondary batteries.
[0049] (2) Manufacturing method of ferritic stainless steel for battery components The method for producing a ferritic stainless steel material according to the embodiment of the present invention is not particularly limited as long as it is a method capable of producing a ferritic stainless steel material having the above-mentioned characteristics. For example, a manufacturing method of a ferritic stainless steel material according to an embodiment of the present invention includes a melting and refining step and a casting step. In the casting step, raw materials, auxiliary raw materials, and Al as a deoxidizer are added to a molten steel furnace and heated to produce molten steel, which is then adjusted to a target composition by acid blowing or the like. In the casting step, the molten steel with the adjusted composition is solidified to produce a cast slab. In the melting and refining process and the casting process, the time from the end of heating in the melting and refining process to the start of casting in the casting process is controlled to 30 to 120 minutes, and the temperature lowering rate of the molten steel during that time is controlled to 0.20 to 2.50° C. / min. By carrying out the melting and refining process and the casting process under such conditions, the cleanliness of the oxide-based inclusions and B1-based inclusions can be controlled within a predetermined range.
[0050] If the time from the end of heating in the melting and refining process to the start of casting in the casting process is less than 30 minutes, there is not enough time for the oxides in the molten steel to float and be removed, and the amount of oxide-based inclusions increases. Also, if the time from the end of heating in the melting and refining process to the start of casting in the casting process exceeds 120 minutes, the amount of alumina (B1-based inclusions) generated by the drop in the temperature of the molten steel increases. If the temperature drop rate of the molten steel exceeds 2.50°C / min, the amount of alumina (B1-based inclusions) generated by the temperature drop of the molten steel increases. If the temperature drop rate of the molten steel is less than 0.20°C / min, the reaction between the refractories constituting the molten steel furnace and the molten steel is accelerated, resulting in an increase in oxide-based inclusions.
[0051] The slab obtained by the casting process can be processed into various shapes by processing it by a known method. For example, when manufacturing a ferritic stainless steel plate, it is processed into a plate shape as follows. First, the slab is hot-rolled to obtain a hot-rolled material. Then, the hot-rolled material is annealed, pickled, and cold-rolled in sequence to obtain a cold-rolled material. After the cold rolling, existing treatments (e.g., surface polishing, temper rolling, treatment with a tension leveler, etc., annealing) may be performed as necessary. Here, each step can be performed using existing equipment, and the conditions may be appropriately adjusted depending on the composition of the stainless steel, and are not particularly limited.
[0052] (3) Battery parts The battery component according to the embodiment of the present invention includes the above-mentioned ferritic stainless steel material, which has excellent high-temperature fatigue properties, and therefore has excellent resistance to thermal runaway when the battery is subjected to an impact due to a collision accident or the like. The battery components are not particularly limited, but examples thereof include a battery case, a battery pack, a battery module, a battery cover, etc. Among these, the battery components according to the embodiment of the present invention are preferably case members and lid members of a lithium ion secondary battery. The manufacturing method of the battery components is not particularly limited, but may be any known method such as a deep drawing method, a welding method, etc. The type of welding in the welding method is not particularly limited, but may be any known method such as TIG welding, laser welding, or electric resistance welding. EXAMPLES
[0053] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these. A ferritic stainless steel sheet was prepared according to the following procedure. First, raw materials, auxiliary materials, and Al as a deoxidizer were added to a molten steel furnace, which was heated to produce molten steel, which was then adjusted to the composition shown in Tables 1A and 1B (the balance being Fe and impurities) by acid blowing or the like, and a casting process was carried out under the conditions shown in Tables 2A and 2B for the time from the end of heating in the melting and refining process to the start of casting in the casting process, and the rate of temperature reduction of the molten steel during that time. A slab was then obtained by heating the slab at 1150°C for 1 hour and hot rolling it, followed by pickling, cold rolling, annealing at 950°C for 1 minute, and pickling, in that order, to produce a cold-rolled annealed sheet (ferritic stainless steel sheet) with a thickness of 0.50 mm.
[0054] [Table 1A]
[0055] [Table 1B]
[0056] [Table 2A]
[0057] [Table 2B]
[0058] The ferritic stainless steel sheets obtained above were subjected to the following evaluations.
[0059] <Cleanliness of oxide inclusions and B1 inclusions> Test pieces were taken from ferritic stainless steel sheets in accordance with JIS G0555:2020, and the cleanliness of oxide-based inclusions and B1-based inclusions was determined by the point counting method specified in Annex JA of JIS G0555:2020. The point counting method involves inserting a glass plate with 20 grid lines each vertically and horizontally into the eyepiece of a microscope, randomly inspecting the test surface, and counting the number of lattice point centers occupied by inclusions. The measurement field was 60 fields randomly selected from the cross section of the ferritic stainless steel sheet in the rolling direction, and the microscope magnification was 400x. The area percentage (%) occupied by each inclusion was calculated using the following formula based on the total number of lattice points on the glass plate within the field, the number of fields, and the number of lattice point centers occupied by each inclusion, and this was used as the cleanliness of each inclusion. Cleanliness of oxide inclusions or B1 inclusions = n / (p×f)×100 In the formula, p is the total number of lattice points on the glass sheet within the field of view, f is the number of fields of view, and n is the number of lattice point centers occupied by all inclusions (all oxide-based inclusions or all B1-based inclusions) in f fields of view.
[0060] <High temperature fatigue properties> Assuming the introduction of strain due to processing or a collision accident, the ferritic stainless steel sheet was bent (a) 90° along the width direction, (b) returned to flat (initial state), (c) bent 90° in reverse (i.e., bent 90° in the opposite direction to (a)), and (d) returned to flat (initial state). From the ferritic stainless steel sheet that had been bent and bent back, a No. 1 test piece described in JIS Z 2275:1978 was taken so that the rolling direction was the longitudinal direction and the bent and bent back processed part was located in the longitudinal center of the test piece, and a high-temperature fatigue test was performed using a Schenk-type plane bending fatigue tester manufactured by Tokyo Koki Testing Instruments Co., Ltd. The conditions for the high-temperature fatigue test were an amplitude stress of 180 MPa or more and a load repetition rate of 1700 cycles per minute. In addition, the high-temperature fatigue test was performed at 300°C and 600°C, assuming a process in which the surrounding batteries heated by a thermal runaway battery are deformed by high-temperature fatigue, and further thermal runaway occurs and spreads. In this evaluation, at both 300°C and 600°C, those that did not break after 300,000 cycles were represented as ◎, those that broke after 300,000 cycles but not after 100,000 cycles were represented as ○, and those that broke after 100,000 cycles were represented as ×. The above evaluation results are shown in Tables 3A and 3B.
[0061] [Table 3A]
[0062] [Table 3B]
[0063] As shown in Tables 3A and 3B, Test Nos. 1 to 17 (invention examples) had good high-temperature fatigue properties because the composition, the cleanliness of oxide inclusions and B1 inclusions were within the prescribed ranges.
[0064] In contrast, in Test No. 18 (Comparative Example), the C content was too high, so that fixation of C was insufficient, leading to sensitization and deterioration of high-temperature fatigue properties. In Test No. 19 (Comparative Example), the N content was too high, so that N fixation was insufficient, leading to sensitization and deterioration of high-temperature fatigue properties. In Test No. 20 (Comparative Example), the Si content was too high, so that the toughness was reduced and the high-temperature fatigue properties were also reduced. Test No. 21 (comparative example) did not contain Si, and therefore the high-temperature fatigue properties were deteriorated. In Test No. 22 (Comparative Example), the contents of Mn, P and S were too high, so that the toughness was reduced and the high-temperature fatigue properties were deteriorated. In Test No. 23 (Comparative Example), the Cr content was too high, so that the toughness was reduced and the high-temperature fatigue properties were also reduced. In Test No. 24 (Comparative Example), the Cr content was too low, so that sufficient high-temperature strength could not be ensured, and the high-temperature fatigue properties were deteriorated. In Test No. 25 (Comparative Example), the Ni content was too high, so that the toughness was reduced and the high-temperature fatigue properties were also reduced.
[0065] Test No. 26 (comparative example) did not contain Ni, and therefore was unable to ensure sufficient high-temperature strength, resulting in a deterioration in high-temperature fatigue properties. In Test No. 27 (Comparative Example), the Cu content was too high, so that the toughness was reduced and the high-temperature fatigue properties were also reduced. Test No. 28 (comparative example) did not contain Cu, and therefore was unable to ensure sufficient high-temperature strength, resulting in a deterioration in high-temperature fatigue properties. In Test No. 29 (Comparative Example), the Ti content was too high, so that the amount of coarse carbonitrides increased and the high-temperature fatigue properties deteriorated. In Test No. 30 (Comparative Example), the Ti content was too low, so that fixation of C and N was insufficient, leading to sensitization and deterioration of high-temperature fatigue properties. In Test No. 31 (Comparative Example), the Nb content was too high, so that the amount of coarse carbonitrides increased and the high-temperature fatigue properties deteriorated. In Test No. 32 (Comparative Example), the Al content was too high, so the cleanliness of the oxide-based inclusions and B1-based inclusions could not be controlled within a predetermined range, and the high-temperature fatigue properties were deteriorated. In Test No. 33 (Comparative Example), the Al content was too low, which resulted in insufficient deoxidation and an increased S content, resulting in a deterioration in high-temperature fatigue properties. In Test No. 34 (Comparative Example), the Ti+Nb content exceeded 0.340 mass %, so that the amount of coarse carbonitrides increased and the high-temperature fatigue properties deteriorated. In Test No. 35 (Comparative Example), the Ti+Nb content was less than 7.7 (C+N), and therefore fixation of C and N was insufficient, leading to sensitization and deterioration of high-temperature fatigue properties.
[0066] In Test Nos. 36 and 37 (Comparative Examples), the time until the start of casting in the casting process was not within an appropriate range, so the cleanliness of the oxide-based inclusions or B1-based inclusions could not be controlled within the specified range, and the high-temperature fatigue properties were degraded. In Test Nos. 38 and 39 (Comparative Examples), the temperature lowering rate of the molten steel was not within an appropriate range, so the cleanliness of the oxide-based inclusions or B1-based inclusions could not be controlled within a predetermined range, and the high-temperature fatigue properties were degraded. In Test Nos. 40 to 43 (comparative examples), both the time until the start of casting in the casting process and the rate at which the temperature of the molten steel was lowered were not within appropriate ranges, so the cleanliness of the oxide-based inclusions and B1-based inclusions could not be controlled within the specified range, and the high-temperature fatigue properties were degraded.
[0067] As can be seen from the above results, the present invention can provide a ferritic stainless steel material for battery components having excellent high-temperature fatigue properties, a method for producing the same, and a battery component.
Claims
1. The alloy contains, on a mass basis, C: 0.001-0.020%, N: 0.001-0.020%, Si: 0.01-0.60%, Mn: 0.01-0.70%, P: 0.001-0.050%, S: 0.0001-0.0014%, Cr: 9.5-18.5%, Ni: 0.001-0.700%, Cu: 0.001-1.200%, Ti: 0.03-0.27%, Nb: 0.001-0.200%, Al: 0.003-0.180%, and the balance being Fe and impurities; The cleanliness of oxide-based inclusions measured by the point counting method specified in Annex JA of JIS G0555:2020 is 0.004 to 0.200%, B 1 The cleanliness of the inclusions is 0.100% or less, A ferritic stainless steel material for battery components that satisfies the following formula (1): 7.7×(C+N)≦Ti+Nb≦0.340 (1) In the formula, each element symbol represents the content (mass %) of each element.
2. On a mass basis, Mo: 0.01 to 2.50%, V: 0.01 to 0.50%, Zr: 0.01 to 0.50%, B: 0.0001 to 0.0050%, Ca: 0.0001 to 0.0100%, W: 0.01 to 2.50%, Sn: 0.01 to 0.50%, Co: 0.01 to 0.50%, Mg: 0.0001 to 0.0100%, Sb:
2. The ferritic stainless steel material for battery components according to claim 1, further comprising one or more selected from the group consisting of 0.001 to 0.300%, REM: 0.001 to 0.500%, Ga: 0.0001 to 0.3000%, Ta: 0.001 to 1.000%, Hf: 0.001 to 1.000%, and Bi: 0.001 to 0.200%.
3. On a mass basis, Si: 0.01 to 0.50%, Cr: 9.5% or more and less than 18.0%, Ti: 0.10% or more and less than 0.25%, Nb: 0.001% or more and less than 0.100%, The cleanliness of the oxide inclusions is 0.004 to 0.125%, B 1 3. The ferritic stainless steel material for battery components according to claim 1, wherein the cleanliness of inclusions is 0.050% or less.
4. The ferritic stainless steel material for battery components according to claim 1 or 2, having a thickness of 0.20 to 1.00 mm.
5. 3. The ferritic stainless steel material for battery components according to claim 1, wherein the battery component is a lid member for a lithium ion secondary battery.
6. A method for producing the ferritic stainless steel material for battery components according to claim 1 or 2, comprising the steps of: The method includes a melting and refining process and a casting process, the time from the end of heating in the melting and refining step to the start of casting in the casting step is 30 to 120 minutes, and the temperature of the molten steel is lowered at a rate of 0.20 to 2.50° C. / min during that time.
7. A battery component comprising the ferritic stainless steel material for battery components according to claim 1 or 2.
8. The battery component according to claim 7 , which is a cover member for a lithium ion secondary battery.
Citation Information
Patent Citations
Cooling apparatus for engine with exhaust turbocharger
JP1985090923A
Battery case mounted on electric car
JP1998188922A
Ferritic stainless steel for battery component member
JP2009167486A